Urban Adolescence: The Role of Neighbourhood Greenspace in Mental Well-Being - Mueller, Marie A. E.; Flouri, Eirini (Frontiers in Psychology, 2021)
Mental health and well-being in adolescence are associated with many short- and long-term outcomes. The evidence suggests that greenspace may play a role in adolescents’ mental well-being, but we do not know much about the specifics of this link. In this paper, we investigated the role of other factors in the association. In a cross-sectional study, we investigated the role of neighbourhood greenspace in emotional and behavioural outcomes in 11-year-old urban adolescents participating in the UK Millennium Cohort Study (n = 4534). We used linear regression models to test for an association of greenspace with self-esteem, happiness, positive mood, negative mood, and antisocial behaviour. We also investigated effect modification/moderation by garden access, physical activity, and perceived area safety. We did not find a main effect of greenspace, but we did find interaction effects. First, in adolescents without a garden, higher levels of greenspace were associated with lower levels of self-esteem and positive mood. Second, in adolescents who reported lower levels of physical activity, higher levels of greenspace were associated with lower levels of negative mood. Third, in adolescents who perceived their areas to be unsafe, higher levels of greenspace were associated with higher levels of antisocial behaviour. Our findings suggest that merely more greenspace in the neighbourhood may not be sufficient to promote the mental well-being of urban adolescents in the UK. However, greenspace does seem to have an influence under certain conditions which should be investigated further in future studies.